2019
DOI: 10.3390/jmse7050155
|View full text |Cite
|
Sign up to set email alerts
|

Influence Mechanism of Different Flow Patterns on the Softening of Red-Bed Soft Rock

Abstract: As a typical representative of red beds, the softening and disintegration of red sandstone when it encounters water is an important cause of initiated engineering disasters. However, research on the softening of this kind of rock has mainly focused on the still water–rock interaction. There is still a lack of quantitative analysis and a mechanistic explanation for the basic experimental study of dynamic water–rock interactions. Therefore, based on the independently developed multifunctional open channel hydrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…With the development of testing technology and testing methods, more and more scholars begin to pay attention to the influence of water-rock interaction on rock properties after rainwater enters into the rock mass. Liu et al [16] discussed two typical flow patterns on the softening of red sandstone and pointed out that dynamic water-rock interactions have a great effect on rock softening and breaking. Xu et al [17,18] studied the effect of periodic water circulation on rock mass by P-Wave Velocity and found that the water-rock interaction changed the porosity of the rock pores and then affected its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of testing technology and testing methods, more and more scholars begin to pay attention to the influence of water-rock interaction on rock properties after rainwater enters into the rock mass. Liu et al [16] discussed two typical flow patterns on the softening of red sandstone and pointed out that dynamic water-rock interactions have a great effect on rock softening and breaking. Xu et al [17,18] studied the effect of periodic water circulation on rock mass by P-Wave Velocity and found that the water-rock interaction changed the porosity of the rock pores and then affected its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to our preliminary research, the laboratory experimental study on the influences of different flow patterns on the softening of red-bed sandstone shows that different flow patterns have almost the same effect on electron surface migration and rock failure. As the flow of water increased, the alkalinity of the circulating solution became stronger, the speed of stabilization of the ion concentration became faster, the development of the microscopic structure of the corresponding rock became higher, and the decrease in mechanical strength became greater [4]. In view of previous studies on the influence of flow patterns on rock failure, this paper will no longer focus on this aspect.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As a kind of special soft rock (that is, the rock whose strength characteristics and engineering forces conform to the parameters described in the literatures [1,2]) which is easy to soften and collapse in the event of water, it is often encountered in major engineering construction efforts, such as the Gezhouba hydraulic engineering project, the Three Gorges Reservoir area, and the South-North Water Transfer Project [3]. Many factors affect rock softening, including the temperature, confining pressure, porosity, and water content [4]. Currently, with the prominent problem of rock engineering in high-temperature environments, the influence of temperature on the mechanical properties of rock has become an important research direction.…”
Section: Introductionmentioning
confidence: 99%
“…Time-dependent failure is common in soft rock [1][2][3], and at times, 70% of the engineering deformation is caused by creep [4]. Recently, many geological disasters in Tibet and the Three Gorges of China are related to uncontrollable soft rock creep, so it is important to study the creep behavior of soft rock [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%